Role of Estrogen Receptor Alpha rs3798577 Polymorphism in Breast Carcinoma Risk Determination - Pieri Kumaladewi; Wirsma Arif Harahap; Bastian Nova; Irianiwati Widodo; Ramadhan Karsono; Ferry Sandra; Bethy Suryawathy Hernowo (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Interaction between estrogen and estrogen receptor (ER) takes part in the regulation and differentiation of breast tumorigenesis. Some ERα polymorphisms, including ERα rs3798577, are reported to be associated with the risk and aggressiveness of breast carcinoma since the site was reported to be targeted by microRNA, which can further modulate the ERα expression. Hence, this study was conducted to disclose the possible role of ERα SNP rs3798577 on breast carcinoma patients.METHODS: Samples were taken from the post-mastectomy breast carcinoma tissues of female patients and screened based on the completeness of medical and histopathological records. DNA isolation was proceeded using real time-polymerase chain reaction (RT-PCR) then analyzed for high resolution melting (HRM). The nucleotide base sequence was then analyzed based on rs3798577 ERα polymorphism. ER immunohistochemistry test was carried out and counted quantitatively based on the staining intensity and the percentage of the stained cells.RESULTS: Out of 65 samples, there were 33 samples as wild type and 32 samples as variant type. Most variant and wild type had >80% ERα percentage. Most variant type had middle ERα intensity, while wild type had strong ERα intensity. Higher percentage of variant type (52.2%) was found with weak ERα histoscore, meanwhile higher percentage of wild type (52.4%) was found with strong ERα histoscore, but not significant (p=0.725).CONCLUSION: ERα rs3798577 variant type had a lower ERα intensity and weaker ERα histoscore compared to the wild type, suggesting that ERα rs3798577 polymorphism might play a role in breast carcinoma risk determination.KEYWORDS: breast cancer, ERα, rs3798577, polymorphism, immunoexpression